Prospective evaluation of respiratory exacerbations in children with cystic fibrosis from newborn screening to 5 years of age. Issue 7 (23rd January 2013) - Byrnes, Catherine Ann; Vidmar, Suzanna; Cheney, Joyce L; Carlin, John B; Armstrong, David S; Cooper, Peter J; Grimwood, Keith; Moodie, Marj; Robertson, Colin F; Rosenfeld, Margaret; Tiddens, Harm A; Wainwright, Claire E; et al.
Abstract : Background: Newborn screening allows novel treatments for cystic fibrosis (CF) to be trialled in early childhood before irreversible lung injury occurs. As respiratory exacerbations are a potential trial outcome variable, we determined their rate, duration and clinical features in preschool children with CF; and whether they were associated with growth, lung structure and function at age 5 years. Methods: Respiratory exacerbations were recorded prospectively in Australasian CF Bronchoalveolar Lavage trial subjects from enrolment after newborn screening to age 5 years, when all participants underwent clinical assessment, chest CT scans and spirometry. Results: 168 children (88 boys) experienced 2080 exacerbations, at an average rate of 3.66 exacerbations per person-year; 80.1% were community managed and 19.9% required hospital admission. There was an average increase in exacerbation rate of 9% (95% CI 4% to 14%; p<0.001) per year of age. Exacerbation rate differed by site (p<0.001) and was 26% lower (95% CI 12% to 38%) in children receiving 12 months of prophylactic antibiotics. The rate of exacerbations in the first 2 years was associated with reduced forced expiratory volume in 1 s z scores. Ever having a hospital-managed exacerbation was associated with bronchiectasis (OR 2.67, 95% CI 1.13 to 6.31) in chest CT scans, and lower weight z scores at 5 years of age (coefficient −0.39, 95% CI −0.74 to −0.05). Conclusions: Respiratory exacerbations in young children are markers for progressive CF lung disease and are potential trial outcome measures for novel treatments in this age group.